The Use of Youtube Vlog to Improve The Students’ Listening Skill of MTs Samarinda - Juliati Amalia Lestari (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2019)
The background of research is students have less motivation in learning English and some students feel difficult in understand vocabularies that were pronounced. As a result, they did not know the word and its meaning. It happens because they couldn’t hear the articulation of the word clearly. The objective of this research is to find out is YouTube vlog can improve students’ listening skill of eighth grade at MTs DDI Tani Aman Loa Janan.  The design of this research was Classroom Action Research (CAR) which researcher following Kemmis and McTaggart action research procedures. The subject of this research was students of VIIIB at MTs DDI Tani Aman were about 29 students. The instrument of this research is observation checklist, test, and field note. The result of this research indicates that there was improvement of the students’ listening skill. Most of the students gradually gained good scores at the second cycle. The score of Minimum Mastery Criterion (KKM) of English lesson was 75.00. In the preliminary study there were 2 students or 7.69% students who passed the KKM and mean score of preliminary study was 28.51. Next, the result of the first cycle showed that there were 9 students or 31.03% students who passed the KKM considering their mean score of the test gained 145.47%. next, the result of the second cycle shows that there were 27 students or 96.42% students who passed the KKM which their mean scores derived 88.21 and gained 209.40% of improvement. So, the final result is found that more than 75% students with individual score in listening skill passed the KKM.